Hygrothermal aging effects on axial behaviour of pultruded web–flange junctions and adhesively bonded build-up bridge members. (January 2018) - Xin, Haohui; Mosallam, Ayman; Liu, Yuqing; Wang, Congzhe
Premature local failure of web/flange junctions of the majority of unstiffened commercially produced pultruded fiber-reinforced polymer composites profiles is inescapable due to lack of fiber continuity at the resin-dominated junction zones. This paper focuses on evaluating both short- and long-term behavior of such junctions when subjected to axial tensile stresses. In this study, the axial mechanical behavior of web/flange junctions of pultruded bridge deck components before and after hygrothermal aging effect is investigated. In the experimental phase, axial tensile tests were performed on six different types of pultruded web–flange junctions to assess axial characteristics of each web/flange junction type. In order to evaluate the hygrothermal behavior of such junctions, axial tensile tests were conducted on web/flange junction specimens that were exposed to both fresh water and artificial seawater environments at temperatures of 40℃, 60℃, and 80℃. Several controlling parameters affecting both strength and stiffness of pultruded fiber-reinforced polymer junctions were identified and discussed that include: (i) Junction's web and flange thicknesses, (ii) fillet radius, and (iii) variation of hygrothermal exposure environments. Results of this study indicated that the axial tensile capacity of a pultruded profiles is increased as the thickness of both web and flange increases. Also, it was found that the larger fillet radius of the pultruded fiber-reinforced polymer profile may contribute to a larger axial tensile capacity of pultruded profiles. However, due to variable size and geometry of the resin-rich junction zones and the common manufacturing defects in the form of folded fabric and other fibers misalignment effects, it is difficult to generalize the preceding results. Experimental results also showed that the degradation of web/flange junctions axial tensile strength increases when junctions are exposed to higher temperatures. Also, it was found that the axial tensile characteristics for junctions specimens exposed to freshwater environment are slightly different than those that were exposed to artificial seawater environments.